Interaction between animal personality and animal cognition - Carere, Claudio; Locurto, Charles (Current zoology, 2011)
The study of animal personality has attracted considerable attention, as it has revealed a number of similarities in personality between humans and several nonhuman species. At the same time the adaptive value and evolutionary maintenance of different personalities are the subject of debate. Since Pavlov＇s work on dogs, students of comparative cognition have been aware that animals display vast individual differences on cognitive tasks, and that these differences may not be entirely accounted for differences in cognitive abilities. Here, we argue that personality is an important source of variation that may affect cognitive performance and we hypothesise mutual influences between personality and cognition across an individual＇s lifespan. In particular, we suggest that： 1） personality profiles may be markers of different cognitive styles; 2） success or failure in cognitive tasks could affect different personalities differently; 3） ontogenetic changes of personality profiles could be reflected in changes in cognitive performance. The study of such interplay has implications in animal welfare as well as in neuroscience and in translational medicine [Current Zoology 57 （4）： 491-498, 2011].